POLA LANSKAP PERMUKIMAN TRADISIONAL LAMPUNG PEPADUN: STUDI KASUS TIYUH GEDUNG BATIN - Rian Adetiya Pratiwi; Andi Gunawan; Aris Munandar (Berkala Arkeologi, 2019)
Lampungnese are divided into two indigenous groups, namely Lampung Saibatin and Lampung Pepadun. These two groups are still divided based on their inhabited territories. The objectives of this study are to identify the characteristics and elements that form the traditional settlement landscape pattern of Lampungnese Pepadun community, and to analyze their traditional settlement landscape pattern. This research was conducted in Tiyuh (Kampung) Gedung Batin, Blambangan Umpu District, Way Kanan, Lampung. Data were collected from three important main sources, which are customary texts, traditional leaders interviews, and existing settlement artefacts. The collected data was analyzed using historical approach. The results shows that the constituent elements of the traditional Lampung Pepadun settlement consist of traditional buildings (houses, communal buildings (sesat), as well as places of worship), arable land, rivers, residential roads and burial land. Tiyuh Gedung Batin is arranged in a pattern that extends along the river flow with houses facing each other.